Pengaruh Variabel Makroekonomi Dan Ketidakpastian Global Terhadap Neraca Perdagangan Indonesia Tahun 2013-2023 - Badi'atul Ulwiyah; Meliza (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The balance of trade is one of the measures that reflects the extent of a country's economic balance with the outside world. This study aims to evaluate the impact of macroeconomic variables and global uncertainty on Indonesia's trade balance from 2013 to 2023 using the quantitative ARDL approach. Findings indicate that exchange rates, inflation, and global uncertainty significantly affect the trade balance in the short term, but do not have the same impact in the long term. Specifically, exchange rates have a significant positive impact, inflation also has a significant positive impact, while global uncertainty has a significant negative impact. However, interest rates and GDP do not have a significant influence on Indonesia's trade balance in both the short and long term. This research provides valuable insights for Indonesian economic and trade policies to address global challenges and enhance the country's trade balance.